1999
DOI: 10.1080/095851999340521
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender and location on the willingness to accept overseas assignments

Abstract: Business students in two universities were queried regarding their willingness to accept international postings. In contrast to Adler' s (1984aAdler' s ( , 1986) ® ndings, gender was a signi® cant predictor when speci® c referent countries were identi® ed. Country characteristics considered here included cultural distance (or the difference between the cultures of the respondent' s home country and that of the referent location) and the levels of development and political risk in the referent country. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…Contrary to Brett's et al (1993) and Aryee's et al (1996) findings (where gender was not a significant predictor), women are significantly more reluctant to accept expatriate assignments than men, especially in a culturally dissimilar host country. It should be noted that Lowe et al (1999) also notice the H1…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Contrary to Brett's et al (1993) and Aryee's et al (1996) findings (where gender was not a significant predictor), women are significantly more reluctant to accept expatriate assignments than men, especially in a culturally dissimilar host country. It should be noted that Lowe et al (1999) also notice the H1…”
Section: Discussionmentioning
confidence: 86%
“…The small number of female expatriates can be attributed to the lack of opportunities presented to them as compared to their male counterparts and the low rate has little to do with their unwillingness to work overseas. In a study conducted by Lowe et al (1999), it is found that males and females consistently differ in their willingness to relocate to specific referent locations. This indicates that country characteristic is a significant predictor of receptivity towards expatriate assignments, especially for females.…”
Section: International Postingsmentioning
confidence: 99%
“…In line with prior research on the determinants of individuals' expatriation intentions (e.g., Engle et al, 2015;Froese, Jommersbach, & Klautzsch, 2013;Lowe, Downes, & Kroeck, 1999;Mol et al, 2009;Remhof, Gunkel, & Schlaegel, 2014), we used business students as sampling units to ensure comparability across samples and with previous studies (e.g., Bello, Leung, Radebaugh, Tung, & Van Witteloostuijn, 2009;Tsui, Nifadkar, & Ou, 2007). Student samples are more homogenous than non-student samples (van de Vijver & Leung, 1997), and thus, reduce the impact of influencing factors other than national context, such as socioeconomic status, education, work experience, and age.…”
Section: Samples and Measuresmentioning
confidence: 98%
“…Nonetheless, several studies have kept locating the main barrier to women's presence in international positions in their own gender identity. They have investigated women's lack of interest in these positions (Linehan & Walsh, 1999), their unwillingness to relocate and to move their family (Lowe, Downes, & Kroeck, 1999), and the influence of dual careers and children on women's decision to accept international assignments (Stroh et al, 2000).…”
Section: Myth One: Gender As a Structural Constraintmentioning
confidence: 99%